Tree crop interactions, productivity and physiological efficiency of understorey crops in Alnus nepalensis and Gmelina arborea based agroforestry systems in Eastern Himalayas - Rangappa, Krishnappa; Singh, Nongmaithem Raju; Janyanaik Joga, Rajappa; Mohapatra, Kamal Prasad; Chandra, Puran; Choudhury, Burhan U.; Moiranghtem, Prabha; Debnath, Supriya; Chanu, L. Joymati; Devi, Ningthoujam Peetambari; Singh, Nongmaithem Uttam; Hazarika, Samarendra; et al. (Frontiers in Sustainable Food Systems, 2025)
Climate change, land degradation, and shrinking land resources are major limitations for increasing crop productivity in the East Himalayan Region (EHR). Agroforestry having a plethora of complementarities is a preferable land-use option for improving agricultural productivity while conserving the natural resources. The effects of agroforestry systems with Gamhari (Gmelina arborea) (GAFS) and Alder (Alnus nepalensis) (AAFS) as tree components, on the soil nutrients, physiological characteristics, and productivity of turmeric (Curcuma longa L.), elephant foot yam (Amorphophallus paeoniifolius), and colocasia (Colocasia esculenta), were assessed in a split plot design with trees in the main plots and understorey crops in sub-plots. The hypothesis of the study was the tree components had enriched the soils and favorably influenced physiological attributes of the understorey crops, enhancing the yields and maximising systems productivities. AAFS canopy had a higher (p < 0.05) leaf area index (LAI = 2.19) than the GAFS (LAI = 1.01). AAFS recorded 32% lower (p < 0.05) photosynthetically active radiation (PAR) than sole crops under treeless conditions (TLS). ANOVA revealed significant interactions (p < 0.01) between tree systems and the understorey crops with their influence on chlorophyll content (SCMR), leaf thickness (LT), stomatal size (SS), stomatal frequency (SF), stomatal conductance (gs), photosynthetic rates (A), transpiration rates (E), intercellular CO2 concentration (Ci), instantaneous water use efficiency (iWUE) and crop yields (YLD). SCMR, SS, SF, gs, iWUE, and YLD in GAFS and AAFS increased significantly (p < 0.05) over TLS, whereas, SF and E significantly decreased (p < 0.05). Regression of physiological traits on yields showed SS (b = 0.0884, p = 0.002), gs (b = 0.00934, p = 0.018), and iWUE (b = 0.2981, p = 0.008) influenced positively, whereas SF (b = −0.0381, p = 0.019) and E (b = −2.304, p = 0.02) negatively impacted the YLD of understorey crops. Alder-turmeric system harnessed the attenuated light with better soil fertility most favorably, supporting high SCMR, low E, high A, high gs to produce higher YLD. Turmeric achieved the highest system productivity (USD 4,281 ha−1 year−1) under the AAFS. Soil pH, organic carbon and nitrogen were significantly enriched (p < 0.05) after 14 years of converting the lands to agroforestry systems. Alder-turmeric was the most effective tree-crop pairing delivering enhanced productivity, soil health and economic returns for sustainable agriculture in the EHR.